СТРУКТУРЫН ЗААГЛАЛЫН БҮСИЙН СУДАЛГААНЫ АСУУДАЛ - Ж. ГАН-ОЧИР; Ц. МӨНГӨНШАГАЙ (Geological Issues, 2023)
It is necessary to investigate region and zones of folding, break and contacts of structure of minerogenetic zoning, geology of fracture zone, internal structure, kinematic and structural syndrome and mineralization of the territory of Mongolia at international and regional level. "Тесtoniс cracks and mineralization” project, Mongolian territory 1:500,000 and scale 1:1000,000 "tectonic fractures" the design of new issues have been raised.